EXPLORING THE IMPACT OF PLANT TERMINOLOGY IN INTERNATIONAL LEXICOGRAPHY - Matkarimova Gulira'no Abdullayevna (World Scientific Research Journal, 2025)
Abstract. In the process of studying phytonyms of any language it is impossible without taking into account their historical features and new genesis. Initially, plants were given names to distinguish them from each other, like any other lexemes, they were elementary payo. Later, some phytonomic names, firmly established in a certain language, became terms. But at the same time, many words expressing the realities of the plant world, passed into the passive reserve (ceased to be used in the language and gave way to neologisms). In this regard, the phytonomic vocabulary of the English language is very important.